The Impact of BI 7-Day Reverse Repo Rate Announcements on the IDX80 Index During 2023 to 2024 - Riska Amelia; Randy Kuswanto (APPS Publications, 2025)
This study examined the impact of Bank Indonesia's 7-Day Reverse Repo Rate (BI-7DRR) change announcements on market reactions among companies listed in the IDX80 index during the 2023-2024 period. The research employs a total sampling method, encompassing all companies included in the IDX80 index throughout the study period. Secondary data were utilized, consisting of daily stock prices, trading volumes, and interest rate data obtained from the official websites of the Indonesia Stock Exchange (IDX) and Bank Indonesia (BI). Data collection was conducted through documentation methods, involving the downloading and recording of relevant data. Secondary data was collected and analyzed using SPSS 25 software through statistical methods. The data analysis process includes several stages: descriptive statistical analysis and wilcoxon signed ranks testing. The results indicate that abnormal returns show no statistically significant differences between pre- and post-announcement periods across all four events, trading volume activity presents a more nuanced pattern. Significant variations in trading volume emerge for the first and fourth events, suggesting heightened investor activity following these announcements. In contrast, the second and third events show no observable change in trading volume, indicating potentially different market perceptions or contextual factors influencing these particular announcements.